Kinerja Kualitas Layanan Logistik dalam Menciptakan Word of Mouth dan Repurchase Intention - Hardiyansyah Hardiyansyah; Cecep Budiman (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
This study aims to examine the service quality performance to creat word of mouth and repurchase intentions in freight forwarding companies in Jakarta. The method of collecting data using a questionnaire and distributed to 150 people who are shipping services in Jakarta. The analysis method uses path analysis and mediation testing. All data are is valid, reliable and normally distributed. The results showed that there was an effect on the quality of logistics service quality in creating positive word of mouth and repurchase behavior in freight forwarding companies in Jakarta.